Growth regimes of populist governments: a comparative study on Hungary and Poland - Julia Kühnast (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2024)
This paper aims to contribute to the debate of post-Keynesian growth models and the political economy of populism by investigating the relationship between the changes in demand and growth regimes and the politics of the right-wing populist governments in Poland and Hungary after the Global Financial Crisis (GFC). In both countries, the GFC was a turning point, leading to the emergence of new economic and political ideas. These processes resulted in changes in the growth regimes and increased the importance of the export sector.
Keywords: E12; E65; F40; F43; G01; O57; 330; growth regimes; populism; comparative political economics